Speedy research-and-development - how beneficial - Ellis, Lynn W; Curtis, Carey C (Research-technology Management, 1995)
As companies increasingly try to do more with less, one of the key prescriptions in the literature has been to employ practices that shorten time to market, including the time taken in R&D. This article reports on survey research that links cycle times and financial performance, and records executives reactions to the results. The main finding is that the reduced costs of faster cycles fail to show up in improved earnings, and suggests several reasons why this occurs. For companies forced by competition to speed up their cycles, several management methods are given for reducing time with minimal financial impairment.
Keywords: dept.acc